2019
DOI: 10.1123/kr.2019-0043
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing the Impact of Bias in Faculty Recruitment, Retention, and Advancement Processes

Abstract: Bias, an automatic—usually unconscious and unintentional—inclination, preference, or favoring of an individual or group over another, is an inherent aspect of an individual’s academic leadership and decision-making processes. Bias alone is not a detriment to building an inclusive and supportive environment for faculty. However, oftentimes an academic unit leader’s biases result in the justification, rationalization, and facilitation of exclusionary processes and practices toward faculty, particularly those fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…27,41,42 Finally, institutions also reported that they faced biases in the selection process or a lack of diversity in the selection committees when recruiting HURE faculty. [43][44][45] The main question at this point is which recommendations can be made for interventions to overcome these challenges and increase best practices for increasing the diversity and inclusion of dental faculty members from HURE backgrounds.…”
Section: Challenges To Increasing the Percentages Of Faculty From Hur...mentioning
confidence: 99%
“…27,41,42 Finally, institutions also reported that they faced biases in the selection process or a lack of diversity in the selection committees when recruiting HURE faculty. [43][44][45] The main question at this point is which recommendations can be made for interventions to overcome these challenges and increase best practices for increasing the diversity and inclusion of dental faculty members from HURE backgrounds.…”
Section: Challenges To Increasing the Percentages Of Faculty From Hur...mentioning
confidence: 99%
“…One organizational approach to reducing implicit racial bias is to address recruitment policies and develop an inclusive environment that helps retain diverse staff. A recent article provides recommendations for institutions to consider when evaluating the influence of implicit racial bias on recruitment, retention, and advancement processes [ 66 ]. An example of the recommendations includes assessing the use of language in recruitment materials, considering where job opportunities are advertised, improving faculty reviewing processes to recognize talent within the diverse staff and provide clear information, mentoring, and support regarding formal processes for promotion (see [ 66 ], for all recommendations).…”
Section: Current Interventions and Recommendationsmentioning
confidence: 99%
“…A logical response from many academic institutions has been to train search committee members to understand how implicit biases structure decisions and become aware of their own narrow lenses (Fraser & Hunt, 2011 ; Russell et al, 2019 ). Scholars who conducted a systematic review of bias in faculty hiring drew on the insights of behavioral economics to suggest how bias reduction “nudges” can slow committee members’ automatic judgments and introduce space for more deliberate thinking (O’Meara et al, 2020 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%